Coagulopathy in COVID‐19. (21st July 2020) - Iba, Toshiaki; Levy, Jerrold H.; Levi, Marcel; Thachil, Jecko
Abstract: The COVID‐19 pandemic has become an urgent issue in every country. Based on recent reports, the most severely ill patients present with coagulopathy, and disseminated intravascular coagulation (DIC)‐like massive intravascular clot formation is frequently seen in this cohort. Therefore, coagulation tests may be considered useful to discriminate severe cases of COVID‐19. The clinical presentation of COVID‐19‐associated coagulopathy is organ dysfunction primarily, whereas hemorrhagic events are less frequent. Changes in hemostatic biomarkers represented by increase in D‐dimer and fibrin/fibrinogen degradation products indicate the essence of coagulopathy is massive fibrin formation. In comparison with bacterial‐sepsis‐associated coagulopathy/DIC, prolongation of prothrombin time, and activated partial thromboplastin time, and decrease in antithrombin activity is less frequent and thrombocytopenia is relatively uncommon in COVID‐19. The mechanisms of the coagulopathy are not fully elucidated, however. It is speculated that the dysregulated immune responses orchestrated by inflammatory cytokines, lymphocyte cell death, hypoxia, and endothelial damage are involved. Bleeding tendency is uncommon, but the incidence of thrombosis in COVID‐19 and the adequacy of current recommendations regarding standard venous thromboembolic dosing are uncertain.